2016
DOI: 10.1186/s40064-016-3370-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and genotyping of Chlamydia trachomatis in symptomatic male patients from Istanbul, Turkey

Abstract: This study was conducted to determine the prevalence and distribution of urogenital Chlamydia trachomatis genotypes in symptomatic male patients who were referred to the clinics of the Istanbul Faculty of Medicine. Of 419 urogenital swabs, 57 samples (13.6 %) were positive for C. trachomatis. Genotype distribution of C. trachomatis-positive samples identified five genetic variants namely genotype E as the most prevalent (36.4 %), followed by genotype G (23.6 %), H (21.8 %), D (16.4 %) and F (1.8 %). We believe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
(27 reference statements)
0
2
1
2
Order By: Relevance
“…15,39,40 In many countries, these three genotypes have also been reported more commonly in urogenital infections. 38,41 However, our findings were slightly different from reports from some countries. Genotypes D, F, and K are the most prevalent among STD subjects in Thailand, while genotypes F predominate in Mexico and Brazil.…”
Section: Discussioncontrasting
confidence: 99%
“…15,39,40 In many countries, these three genotypes have also been reported more commonly in urogenital infections. 38,41 However, our findings were slightly different from reports from some countries. Genotypes D, F, and K are the most prevalent among STD subjects in Thailand, while genotypes F predominate in Mexico and Brazil.…”
Section: Discussioncontrasting
confidence: 99%
“…In the study of Köksal et al, conducted in Turkey, genotype E was the most common type, but the prevalence of type F was much lower than that of other types, corresponding to only 1.8% of cases. In this study, types G and H were common after type E in terms of prevalence [ 26 ]. These results showed that the distribution of genotypes in different geographical areas could be different, but the important point is that type E in all studies is one of the most common genotypes of this bacterium, and globally, it seems to be more common than other genotypes of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, the microorganism genotyping is based on ompA sequencing, which is amplified by using the primers that have been described by Jalal and colleagues [ 73 ] and following the protocol that has been detailed by Bianchi et al [ 67 ], in which the amplicons must be purified by using, for example, NucleoSpin ® Extract II (Macherey-Nagel GmbH, Germany) or the Qiaquick PCR Purification Kit (Qiagen, Hilden, Germany). Finally, the automated DNA sequencing can occur on the ABI PRISM 3100 genetic analyzer (Applied Biosystem, CA, USA) [ 67 , 74 ]. Next, a bioinformatic analysis must be performed in order to align the sequences of these samples with the sequences within the databases (NCBI GenBank) using bioinformatic tools, such as ClustalX 2.1 multiple aligner, in order to classify the Chlamydia trachomatis strain [ 55 , 67 , 75 ].…”
Section: Chlamydia Diagnostic Methodsmentioning
confidence: 99%